Freshwater reservoir effects in Cis-Baikal: an overview - Schulting, RJ; Ramsey, CB; Scharlotta, I; Richards, MP; Bazaliiskii, VI; Weber, A (Elsevier, 2021)
This paper summarises research on freshwater reservoir effects (FRE) in the Baikal region and their impact on the radiocarbon dating of human remains. Varying relationships are seen between human δ13C and δ15N values and 14C offsets in paired human-terrestrial mammal radiocarbon dates from the same graves in the different microregions of Cis-Baikal. In the Upper Lena microregion the FRE may also vary through time. These differences can be related in some cases to different isotopic ecologies, and in others to the presence of different old carbon reservoirs. Some areas requiring further research are highlighted, and the use of other proxies (δ2H, δ34S) for assessing the dietary contributions of freshwater resources is considered. A case study from the Early Neolithic cemetery of Shamanka II is used to illustrate the marked effects of changes in dietary catchment over an individual's life history, with bone and tooth dates from the same individual differing by 385 14C yr.